Atuação da Biblioteca Nacional no contexto da censura às obras literárias eróticas: abordagens do período da Ditadura Militar - Franciane Monick Gomes de França (2023)
This research is a case study that aims to investigate and report how the censorship of literary books with erotic/sexual content occurred during the period of the Military Dictatorship (1964-1985), in the Brazilian National Library, as well as the role of Librarians in the face of censorship acts. From the theoretical reference and from a historical perspective, it had been mainly dealt with the following themes: censorship in the dictatorial period and its controlling instituitions, the bibliographic heritage as part of the country's collective memory and legal materials in the library area that had guided the professional ethics that had been performanced by the Librarians at the time. At the methodological level, documentary researches had been used, it had been taken place at the National files, to understand the survey of the censors and its preparation for carrying out the function, through the opinions of its Previous Censorship Series and administrative documents from the General Administration Section, both of them had been part of the Fund for Public Entertainment Censorship Division, the instituition responsible for centralizing censorship in the Military Dictatorship. The documentary research also includes administrative files from the National Library in regards to the dictatorial period, through the National Library Collection, under the custody of the Manuscripts Section, which contains administrative reports, statistic datas, correspondences, letters, and the Annual Management files wich are part of the General Archive and the Management Reports that appear in the Annals of the National Library. The documentary research aims to identify the presence of works examined by the censors, especially those one wich that had been prohibited. As the results, 78 books titles that corresponded to erotic, pornographic, obscene or about sexual education, in portuguese, were identified in the online catalog, from the total list of 673 in the Prior Censorship Series. It had been checked the existence of its files in the dictionary catalogue, used at the time to identify the works that made up the collection. It had been also included in the methodology some interviews and e-mail correspondences with employees of the National Library, resulting in 1 testimony and 3 reports of episodes about government and librarian activities. By analyzing the data collected, it had been found from the 78 books included in the collection that 52 were prohibited, 20 were released and 6 were absent, which 75 of them were acquired by legal deposit. The actions that had been taken by Librarians to protect prohibited publications included hiding them in safes and cabinets, removing identification cards, changing shelves and sections. In terms of government practices, it had been noticed the presence of agents of the dictatorship to supervise these works in an official and camouflaged way. It had been concluded that there was a governmental censorship supervisory action, without legal determination embargoing the acquisition of publications, but seeking to subsequently remove certain articles from the collection, and that on the part of some employees, including Librarians, there were strategies of resistance to censorship and safeguarding of works restrained.